1997
DOI: 10.1159/000266461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Oral Reading on Time-Based Glottal Flow Waveform Parameters with Special Reference to Gender Differences

Abstract: The effects of prolonged (5 × 45 min) reading (loading) on time-based glottal waveform parameters of normal female and male subjects (n = 80) were studied. Two rest (morning and noon) and three loading (two in the morning and one in the afternoon) samples were recorded and analyzed. The glottal waveforms were obtained by inverse filtering of the acoustical signal using an automatic method. The following time-based parameters were analyzed from the estimated glottal flow waveform: (1) length of fundamental peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 16 publications
(28 reference statements)
4
33
0
Order By: Relevance
“…Among performers, females were significantly more likely than males to score higher on all subscales. This finding is in keeping with previous voice research that females are more likely than males to report vocal fatigue symptoms [9,38] and to report voice problems [39], although whether there may be gender-based differences in laryngeal response to vocal load has not been established. The findings for this study do suggest that gender may be an important predictor for the development of vocal pathologies among working MTS.…”
Section: Discussionsupporting
confidence: 89%
“…Among performers, females were significantly more likely than males to score higher on all subscales. This finding is in keeping with previous voice research that females are more likely than males to report vocal fatigue symptoms [9,38] and to report voice problems [39], although whether there may be gender-based differences in laryngeal response to vocal load has not been established. The findings for this study do suggest that gender may be an important predictor for the development of vocal pathologies among working MTS.…”
Section: Discussionsupporting
confidence: 89%
“…Effects of vocal load have been examined in several experiments, differing from one to another in terms of loading task and experimental environment. Some studies have observed the effect of vocal load using a natural speech material, [2][3][4][5][6][7][8][9] whereas others have used a loading task as prolonged loud reading [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] or repeated vowel sequence. 25 The duration and intensity level of such loading tasks have varied across studies as well as the moment and duration of recordings.…”
Section: Introductionmentioning
confidence: 99%
“…Voice samples have been analyzed either throughout the vocal load using audiotape recorders 4,7,14 and dosimeters or at different times before and after loading. 2,3,[5][6][7][10][11][12][13][15][16][17][19][20][21][22][23][24][25] Some experiments have taken place in a laboratory environment, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] whereas others have studied subject's vocal load, during the working day. [2][3][4][5][6][7][8][9] The present study has been initiated to improve the understanding of voice duration and intensity level as loading factors.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used time-based parameters are open quotient (OQ), speed quotient (SQ), and closing quotient (ClQ). [7][8][9][10][11][12] The amplitudebased parameters typically extracted are minimum flow (also called the dc offset), the ac flow, and the negative peak amplitude of the flow derivative (d min ), also called maximum airflow declination rate. 7,10,[12][13][14] It is also possible to define time-based parameters from amplitude measures by using, for example, the amplitude quotient (AQ) and its normalized version, the normalized amplitude quotient (NAQ).…”
Section: Introductionmentioning
confidence: 99%
“…Different phenomena of voice production have been studied by concentrating on issues like phonation type, 17 intensity, 8 voice quality, 18 emotions, 19 pitch, 7,12 disturbed voice functions, 10,[20][21][22][23][24][25] singing styles, 16,[26][27][28] and vocal loading. 9,29,30 In addition, some studies have discussed IF from a methodological point of view. 6,31 Given the prevalence of IF in the field of voice science, it is surprising that the differences between IF methods have not yet been studied extensively.…”
Section: Introductionmentioning
confidence: 99%